A social systems analysis of implementation of El Salvador's national HIV combination prevention: a research agenda for evaluating Global Health Initiatives - Julia Dickson-Gomez; Laura A. Glasman; Gloria Bodnar; Molly Murphy (BMC, 2018)
Abstract Background Global Health Initiatives (GHIs) have been instrumental in the rapid acceleration of HIV prevention, treatment access, and availability of care and support services for people living with HIV (PLH) in low and middle income countries (LMIC). These efforts have increasingly used combination prevention approaches that include biomedical, behavioral, social and structural interventions to reduce HIV incidence. However, little research has evaluated their implementation. We report results of qualitative research to examine the implementation of a national HIV combination prevention strategy in El Salvador funded by the Global Fund to Fight AIDS, Tuberculosis and Malaria. Methods We conducted in-depth interviews with principal recipients of the funding, members of the Country Coordinating Mechanism (CCM) and front line peer outreach workers and their clients. We analyzed the data using a dynamic systems framework. Results El Salvador's national HIV combination prevention strategy had three main goals: 1) to decrease the sexual risk behaviors of men who have sex with men (MSM), commercial sex workers (CSW) and transgender women (TW); 2) to increase HIV testing rates among members of these populations and the proportion of PLH who know their status; and 3) to improve linkage to HIV treatment and adherence to antiretroviral therapy (ART). Intervention components to achieve these goals included peer outreach, community prevention centers and specialized STI/HIV clinics, and new adherence and retention protocols for PLH. In each intervention component, we identified several factors which reinforced or diminished intervention efforts. Factors that negatively affected all intervention activities were an increase in violence in El Salvador during implementation of the strategy, resistance to decentralization, and budget constraints. Factors that affected peer outreach and sexual risk reduction were the human resource capacity of grassroots organizations and conflicts of the national HIV strategy with other organizational missions. Conclusions Overall, the national strategy improved access to HIV prevention and care through efforts to improve capacity building of grass roots organizations, reduced stigma, and improved coordination among organizations. However, failure to respond to environmental and organizational factors limited the intervention's potential impact.